A comparison of manual versus automated saturation of peripheral oxygenation in the neonatal intensive care unit. (18th May 2016) - Das, Anirudha; Mhanna, Maroun; Teleron-Khorshad, Amy; Houdek, John; Kumar, Nitin; Gunzler, Douglas; Collin, Marc
Abstract: Background : It is vital to maintain the saturation of peripheral oxygenation (SpO2 ) in a targeted range in extremely premature infants to improve survival without significant morbidities. Objectives : To compare manual versus automated monitor documentations of daily upper and lower values of SpO2 in premature infants. Methods : In a prospective observational study, the highest and lowest daily SpO2 manually recorded values from electronic medical records were compared with automatically recorded values from bedside cardiorespiratory monitors. Results : Eighteen infants were monitored for 605 patient days, with a mean birth weight of 859 ± 183 g, and gestational age of 26.0 ± 1.3 wks. Within the lowest SpO2 values, manually recorded values were consistently higher than the simultaneous automatically recorded monitor values. The highest SpO2 point differences in documentation was seen in patients with SpO2 range ≤ 70% (16 ± 13 points), followed by 71–80% (10 ± 7 points) and 81–90% (7 ± 4 points); p < 0.01. Conclusions : The difference between manually and automatically recorded SpO2 is large in lower SpO2 ranges and small in higher SpO2 ranges. Automated oxygen administering systems should be considered to reduce potential errors.